2022
DOI: 10.1002/cam4.5148
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscape of homologous recombination‐related genes in small‐cell lung cancer

Abstract: Background Homologous recombination deficiency (HRD) is a well‐known biomarker which could predict poly‐ADP ribose polymerase 1 (PARP) inhibitor and platinum drug response. As an aggressive cancer, small‐cell lung cancer (SCLC) is sensitive to platinum drugs, but relapse occurs rapidly. Herein, we aim to illustrate the genomic alteration patterns of homologous recombination repair (HRR)‐related genes in a Chinese SCLC cohort and further analyze the relationship among HRR gene mutations and known biomarkers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…Deleterious DDR mutations have been reported to be associated with high TMB in solid tumors including lung cancer 10,16,26,29‐34 . In this study, we found that deleterious alterations in the DDR pathway were associated with a higher number of gene mutations, and we also observed significantly higher TMB in the DDR‐mut subgroup in the pan lung cancer dataset for both the selected 74 DDR genes and six genes.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Deleterious DDR mutations have been reported to be associated with high TMB in solid tumors including lung cancer 10,16,26,29‐34 . In this study, we found that deleterious alterations in the DDR pathway were associated with a higher number of gene mutations, and we also observed significantly higher TMB in the DDR‐mut subgroup in the pan lung cancer dataset for both the selected 74 DDR genes and six genes.…”
Section: Discussionsupporting
confidence: 59%
“…Deleterious DDR mutations have been reported to be associated with high TMB in solid tumors including lung cancer. 10,16,26,[29][30][31][32][33][34] In this study, we found that deleterious alterations in the DDR pathway were associated with a higher number of gene mutations, and we also observed significantly higher TMB in the DDR-mut subgroup in the pan lung cancer dataset for both the selected 74 DDR genes and six genes. It has been reported that deleterious DDR gene mutations are an independent predictor of better response to immune checkpoint inhibitors in colorectal cancer 15 and NSCLC.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Of the DNA damage response and repair genes frequently mutated in NSCLC, ATM mutations are the most prevalent occurring in ~9% of LUAD and ~4% of lung squamous cell carcinoma based on The Cancer Genome Atlas (TCGA) cohorts ( 7 , 8 ). They are also found in ~8% of small cell lung cancers ( 9 ). Unlike commonly mutated oncogenes, ATM mutations are not localized to specific amino acids or functional domains, and are instead scattered throughout the ATM gene which spans ~150 kilobases.…”
Section: Atm Variants In Non-small Cell Lung Cancer (Nsclc)mentioning
confidence: 99%